ANALISIS KASUS SEDIMENTASI DI TIGA TITIK KAWASAN WATER FRONT CITY - Yuda Romdania (UNIVERSITAS LAMPUNG, 2010)
Prediction of sediment transport along the coast for various conditions is very important to knowin order to know the amount of sediment transport and examine the influences that tend toprovoke. Existence of the buildings on the coast will cause sedimentation in one hand and on theother side causing erosion. Bandar Lampung is city with a coastal region, is currently designing ajob that is Water Front City (beach city) which is designed in an effort to carry out vision andmission of Bandar Lampung City which is